Welfare dependence: Concepts, measures, and trends - Moffitt, Robert; Gottschalk, Peter (American Economic Review, 1994)
In the past ten years, discussions of the system and reform have increasingly been concerned with the extent of welfare dependence. However, while the idea that some individuals may be dependent upon the system for support is intuitively clear, the concept of dependence is rather ill-defined. Our aims in this paper are to clarify what is meant by dependence; to discuss the implications for data handling, measurement, and statistical modeling; and to present new results on the level and trend in dependence in the United States.